Pseudocontingencies. (article). - Fiedler, Klaus
In 3 experiments, the authors explored the contingency illusion termed pseudocontingency (PC) that produces logically unwarranted but potentially inferences. PCs arise when bivariate contingencies are inferred from univariate distributions via heuristic alignment processes. For example , the absence of information about co-occurence of TV habits and aggressive behavior within a school class, when the prevalence of both attributes is high, a teacher may inference a positiva PC as if students who often watch TV were highly aggressive. Throughout 3 experiments predictions of the level 1 variable from the level of another served as a measure of PCs. The illusion could evoked reliably whether information about target attributes was presented successfully of simultaneously, whether common-cause or common-effect models were activated, and whether attributes involved of 2 or more levels. The discussion centers on the cognitive processes underlying PCs and their origin and adaptive value. -- (from the author)
Keywords: Psychology-Periodicals.